Clinical Efﬁcacy of Volume Stable Collagen Matrix in the Management of Gingival Recession and Gingival Phenotype Modiﬁcation-A Systematic Review - V., Pooja (2025)
Gingival recession, the apical migration of the gingival margin beyond the cemento-enamel junction, leads to aesthetic and functional problems such as dentinal hypersensitivity and root caries. Volume-stable collagen matrices (VCMX) have been introduced as a less invasive alternative to connective tissue grafts (CTG), offering regenerative potential with reduced morbidity. To evaluate the clinical efficacy of VCMX compared to CTG in managing gingival recession and enhancing gingival phenotype. A systematic search of PubMed, Scopus, ScienceDirect, Cochrane Library, and Google Scholar identified RCTs on adults with Miller’s Class I/II or Cairo’s RT1/RT2 recession. Data extraction and bias assessment were performed independently using Cochrane RoB 2 and ROBINS-I tools, with GRADE applied for evidence quality. Five studies (120 participants, 6 weeks-12 months follow-up) were included. VCMX showed significant reductions in recession depth (RD) and increased keratinized tissue width (KTW), comparable or superior to CTG. Both improved clinical attachment level (CAL), though VCMX offered less postoperative pain and faster recovery. VCMX serves as an effective, minimally invasive alternative to CTG for treating gingival recession, improving patient comfort and reducing morbidity. However, further long-term, multicentre RCTs are needed to validate and standardize its clinical use.